Sedimentary Characteristics of Lacustrine Beach-Bars and Their Formation in the Paleogene Weixinan Sag of Beibuwan Basin, Northern South China Sea - Jie He; Hua Wang; Tao Jiang; Entao Liu; Si Chen; Ping Jiang (Energies, 2022)
Beach-bar reservoirs have been promising hydrocarbon-bearing exploration advances in the Beibuwan Basin, especially in the WZ12-2 area within the Weixinan sag. The sedimentary characteristics, distribution and formation mechanisms of beach-bar sand bodies in Mbr2 (Member 2) of the Paleogene Liushagang Fm. in the WZ12-2 area within the Weixinan sag were analyzed based on well-log, seismic and core data on thin section and heavy mineral data. Mbr2 in the WZ12-2 area comprises a third-order sequence, which consists of three systems tracts (lowstand systems tract, transgressive systems tract and a locally developed highstand systems tract). Thick beach-bar sand bodies are developed in the WZ12-2 area during the lowstand systems tract stage. The formation of sandy beach-bar sand bodies can be divided into five stages. By integrating lithology, mineral composition, sedimentary structures and geophysical characteristics, it can be concluded that the beach-bar sand bodies in the study area were controlled by paleotopography, hydrodynamic environment, sediment provenance and lake-level variation. The gentle slope of the Qixi uplift and relatively stable passive tectonic background during the deposition of Mbr2 of the Liushagang Fm. laid a solid paleogeomorphological foundation for beach-bar deposition. Strong hydrodynamic forces and shallow water further contributed to beach-bar sand bodies formation. In addition, the sands in the fan delta in the northwestern part of the area served as point provenance and the deposits in the southeast acted as linear provenance in providing sediments to the beach-bars. High-frequency variations of the lake level drove vertical stacking of the beach-bar sand bodies and considerable lateral extension over a large area. The sedimentary characteristics and formation mechanism of lacustrine beach-bars in this study may provide a reference for hydrocarbon exploration in other similar basins in the world.